Clinicopathological Study on Hypopharyngeal Carcinoma in Dhaka Medical College Hospital (Bangladesh Journal of Otorhinolaryngology, 2016)
A Cross-Sectional Study was carried out from July 2006 to June 2007 at Department of Otolaryngology and Head-Neck Surgery of Dhaka Medical College Hospital, Dhaka. Data was collected from 150 patients with histologically diagnosed Hypopharyngeal carcinoma. Results of this study showed that hypopharyngeal carcinoma affects more in fifth (36.7%) and sixth (27.4%) decades of life. It was found that male were highly predominant to develop hypopharyngeal carcinoma and male female ratio was 9:1. People with lower educational level were found to be affected more by hypopharyngeal carcinoma. In this study 86 percent patients had history of smoking. Mean duration of smoking was 38.0±23.6 years. This study found that the key symptoms of hypopharyngeal carcinoma was dysphagia, pain and neck mass. In this study 83.5 percent patients presented with palpable lymph node and most (76.6%) of them were in level II. Pyriform fossa was found to be the commonest site (83.3%). In this study all malignancy in hypopharynx was histopathologically squamous cell carcinomaBangladesh J Otorhinolaryngol; October 2015; 21(2): 85-89